Multimodality imaging –PET/CT and PET/MRI: making a difference - Shah, Syed Inayatullah (Research Publish Journals, 2016)
Last decade has witnessed the significant role of hybrid imaging modalities (PET/CT and PET/MRI) in clinical examinations for diagnostic, therapeutic and other health related conditions of humankind. These modalities provide both the information, i.e., functional and anatomical in the single image relating to the organ under study. Thus, diagnostic accuracy and specificity of the disease in many patient studies has enormously increased. Also, confidence level in therapeutic procedures has risen. In this paper, evolution and clinical use of PET/CT and PET/MRI are briefly reviewed.